Exploring the mechanism of analgesic effect of Tuina on alleviating delayed muscle soreness in exercise-induced muscle damaged rats: a combined transcriptome- and non-targeted metabolome-based analysis - Liu, Jiawen; Li, Lunyu; Ayi, Liubu; Li, Zhonghao; Zhang, Ruichi; Yao, Binyu; Xia, Yu; Liu, Qingsong; Ding, Haili (Frontiers in Medicine, 2025)
ObjectivesPrevious research has demonstrated the therapeutic effects of Tuina on exercise-induced muscle damage (EIMD) and its analgesic role in delayed-onset muscle soreness (DOMS). This study aimed to elucidate the molecular mechanisms underlying the analgesic effects of Tuina by analyzing temporal changes in gene expression and metabolite profiles at sites of skeletal muscle injury following intervention.MethodsEighty-eight 8-week-old SD rats were randomly assigned to a control group (C), an exercise group (E) and a Tuina-treated group (T). An EIMD rat model was established to assess the mechanical withdrawal threshold (MWT), Enzyme-linked immunosorbent assay (ELISA) was employed to measure creatine kinase (CK) levels, histological staining and transmission electron microscopy was used to observed skeletal muscle repair post-Tuina treatment. Transcriptomic and metabolomic analyses were performed to assess dynamic changes in gene expression and metabolites at the sites of muscle micro-damage from 0 to 72 h post-intervention.ResultsTuina significantly increased MWT and reduced CK-MM expression in EIMD rats, indicating enhanced skeletal muscle repair. Transcriptomic analysis identified 470 differentially expressed genes (DEGs) at 48 h post-intervention (E48 vs. T48), enriched in pathways like Chemokine signaling, Leukocyte transendothelial migration, and Regulation of actin cytoskeleton. Metabolomic analysis revealed 761 differentially expressed metabolites (DEMs) at 48 h, enriched in pathways including Inflammatory mediator regulation of TRP channels and cAMP signaling. Integrative analysis pinpointed 35 shared KEGG pathways, highlighting key roles for inflammatory regulation (e.g., Ccl2, Itgam), muscle repair (e.g., Igf1), oxidative stress (Ferroptosis pathway), and cAMP signaling.ConclusionTuina alleviates EIMD-associated pain and promotes muscle recovery by modulating inflammatory, promoting tissue repair pathways, inhibiting ferroptosis, and activating cAMP signaling, with the 48 h post-intervention mark representing a critical window for therapeutic effect.